2022
DOI: 10.3389/fcimb.2022.875543
|View full text |Cite
|
Sign up to set email alerts
|

Airway Epithelial Cells Differentially Adapt Their Iron Metabolism to Infection With Klebsiella pneumoniae and Escherichia coli In Vitro

Abstract: BackgroundPneumonia is often elicited by bacteria and can be associated with a severe clinical course, respiratory failure and the need for mechanical ventilation. In the alveolus, type-2-alveolar-epithelial-cells (AECII) contribute to innate immune functions. We hypothesized that AECII actively adapt cellular iron homeostasis to restrict this essential nutrient from invading pathogens – a defense strategy termed ‘nutritional immunity’, hitherto mainly demonstrated for myeloid cells.MethodsWe established an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…The previous studies found that Escherichia coli induces iron retention in A549 cells and causes the corresponding induction of the protein ferritin. This regulation of iron homeostasis may be mediated by oxidative stress ( 56 , 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…The previous studies found that Escherichia coli induces iron retention in A549 cells and causes the corresponding induction of the protein ferritin. This regulation of iron homeostasis may be mediated by oxidative stress ( 56 , 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nrf-2 has previously been shown to be an important regulator in nutritional immunity, depriving intracellular pathogens of iron by enhancing the egress of iron via ferroportin [ 80 ]. Furthermore, Nrf-2 activation upon infection has also been observed in non-professional immune cells, emphasizing the importance of this mechanism [ 81 , 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cells were prepared as described [ 39 ]. On the day of infection, 15 min before S .tm was added at a MOI 10, 0.5 µL of CellROX TM Deep Red (Thermo Fisher, catalog number: C10422) was pipetted to each well.…”
Section: Methodsmentioning
confidence: 99%